2011
DOI: 10.1111/j.1468-2354.2011.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Transportation Costs, Agricultural Productivity, and Cross‐country Income Differences*

Abstract: There are large differences in transportation infrastructure across nations. Constructing a measure of transportation infrastructure density for a large set of countries, I show that the disparity in this measure between the 5% income rich and the 5% income poor countries is a factor of 28. Are these differences a source of productivity differences across nations? Using a three-sector, two-region, general equilibrium model, I show that high transport costs can distort the allocation of resources not only acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…Based on detailed micro data, Donaldson (2016), Atkin and Donaldson (2016), Allen (2014), Asturias et al (2016), and Adamopoulos (2011) quantify the size and nature of intracountry trade frictions for developing countries but do not compare them to international trade frictions. Other work has estimated the regional effects of differential market access within countries on the gains from trade.…”
Section: Related Literaturementioning
confidence: 99%
“…Based on detailed micro data, Donaldson (2016), Atkin and Donaldson (2016), Allen (2014), Asturias et al (2016), and Adamopoulos (2011) quantify the size and nature of intracountry trade frictions for developing countries but do not compare them to international trade frictions. Other work has estimated the regional effects of differential market access within countries on the gains from trade.…”
Section: Related Literaturementioning
confidence: 99%
“…Herrendorf et al (2012) study the effect of the construction of railroads in the US during 1840-1860, and find that the associated reduction in transportation costs lead to settlement of the most fertile land in the Midwest, and a reduction in the agricultural labor force. Adamopoulos (2011) shows that transportation costs can lead to low aggregate output per worker, by reducing productivity within sectors and distorting allocation of resources across locations and between sectors. He analyzes the effect of cross country transportation cost disparities and finds that improvements in transportation productivity would have an asymmetric result on the poor and developed countries, with the former gaining more.…”
Section: Introductionmentioning
confidence: 99%
“…Naudé and Matthee (2007) found that 12 international transport costs to and from African countries to be basically twice as high as the world average. Adamopoulos (2011) found that freight rail is 10 times more expensive in Uganda and Mali than in the United States. He shows that low transport productivity and high transport costs makes agricultural trade in Africa unprofitable and hence contribute to the misallocation of resources, as it limits specialization, and limits the use of sophisticated inputs (see also Kariuki, 2011).…”
Section: Geographical Disadvantagesmentioning
confidence: 99%
“…He shows that low transport productivity and high transport costs makes agricultural trade in Africa unprofitable and hence contribute to the misallocation of resources, as it limits specialization, and limits the use of sophisticated inputs (see also Kariuki, 2011). Using a CGE model Adamopoulos (2011) calculates that if the advanced economies had the same transport productivity of African countries their GDP would be 10 per cent lower.…”
Section: Geographical Disadvantagesmentioning
confidence: 99%